The Effect of NPM, CR, and TATO on Stock Prices with ROA as an Intervening Variable at PT Unilever Indonesia Tbk for the Period 2019-2023 - Hanindhita Nurfhia Syifa; Apriyanti Apriyanti; Maiyaliza Maiyaliza (Rescollacom (Research Collaborations Community), 2025)
PT Unilever Indonesia Tbk (UNVR) is one of the leading business entities in the Indonesian FMCG sector that has been operating since 1933. Although the FMCG sector is growing, UNVR is facing a decline in financial performance in 2019–2023, marked by a net profit that fell from IDR 5.36 trillion (2022) to IDR 4.8 trillion (2023) and stock price fluctuations between IDR 3,530 –IDR 8,400. The main factors affecting the company's performance include the instability of raw material prices, the level of competition in a tight market, and the transformation of consumer behavior. This study aims to analyze the effect of Net Profit Margin (NPM), Current Ratio (CR), and Total Asset Turnover (TATO) on UNVR's stock price, with Return on Assets (ROA) as an intervening variable. The method applied is quantitative through an associative approach, using secondary data from the company's financial statements for the period 2019–2023. The results of the analysis show that the average of NPM reached 0.1478, CR 0.6176, TATO 2.1625, and ROA decreased from 35.80% (2019) to 29.23% (2022). Normality and multicollinearity tests indicate that the regression model meets statistical assumptions. Path analysis with two models (Model 1 without intervening variables and Model 2 with ROA as an intervening variable) proves that Model 2 provides a more comprehensive understanding of the relationship between variables. Although Model 1 has high predictive power, Model 2 explains in more detail the mechanism of the influence of independent variables on stock prices with the mediating role of ROA. This finding indicates that investors are more interested in investing in entities with good profitability, stable liquidity, high asset utilization efficiency, and solid profitability performance, all of which are reflected in ROA. The decline in profit and ROA contributed to stock price fluctuations, influenced by inflation of 5.51% (2022) and e-commerce growth of 2.75% (2023). Based on these results, UNVR needs to improve operational efficiency and digital strategy to improve profitability and market valuation.